Managing Teacher’s Digital Literacy in Responding to the Challenges of 21st Century Skills - Lukman Hakim (STAI Hubbulwathan Duri, 2021)
Digital technology has become a very important part of the implementation of education. Therefore, the purpose of this research was to find out the need for a digital literacy framework for teachers in facing the challenges of 21st-century education. The participants were 30 class teachers and principals from the Karang Baru State Islamic Madrasah, Al-Ittihadul Islamiyah Islamic School Ampenan, and the Integrated Integrated Elementary School Sekarbela. Data were taken using observation, interviews, questionnaires, and documentation. This study uses a descriptive qualitative research approach. The results of the study indicate that teachers need to increase digital literacy in aspects of Information and Information literacy, communication and collaboration, digital content creation, digital security, and digital problem-solving. The implications of this research can be seen in understanding the concept of improving the quality of teacher digital literacy according to the needs of teachers and the situation of the school environment